2011
DOI: 10.1007/s00439-011-1081-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in disease risk from reported genome-wide association study findings

Abstract: Men and women differ in susceptibility to many diseases and in responses to treatment. Recent advances in genome-wide association studies (GWAS) provide a wealth of data for associating genetic profiles with disease risk; however, in general, these data have not been systematically probed for sex differences in gene-disease associations. Incorporating sex into the analysis of GWAS results can elucidate new relationships between single nucleotide polymorphisms (SNPs) and human disease. In this study, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 35 publications
0
56
1
Order By: Relevance
“…Likewise, reanalysis of GWAS datasets revealed that coronary artery diseases, Crohn disease, rheumatoid arthritis, and type1 diabetes show sex-specific associations with increased risk in only 1 gender. [22,23] In the present GWAS, we explored the genetic basis of sex differences by comparing genotype frequencies between male and female cases with childhood ALL using a case-only study design.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, reanalysis of GWAS datasets revealed that coronary artery diseases, Crohn disease, rheumatoid arthritis, and type1 diabetes show sex-specific associations with increased risk in only 1 gender. [22,23] In the present GWAS, we explored the genetic basis of sex differences by comparing genotype frequencies between male and female cases with childhood ALL using a case-only study design.…”
Section: Introductionmentioning
confidence: 99%
“…However, direct comprehensive assessment of SNP-by-sex interactions for BMD has not been previously reported. The availability of large-scale GWAS collaborations allows for massive testing of SNP-by-sex interaction effects (20) and for rigorous replication of proposed discovered interactions that would allay the risk of false positives (21). To study potential genetic contributions to the sexual dimorphism in BMD, we first performed a comprehensive study of genome-wide gene-by-sex interactions in cohorts with both men and women who are part of the Genetic Factors for Osteoporosis (“GEFOS”) consortium.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, either sex stratification or sex adjustment is commonly advised in the epidemiological and molecular analysis of such traits [4][5][6]. For example, sex differences have been reported recently to characterize even well-established disease associations between single nucleotide polymorphisms and both Coronary Artery Disease and Crohn Disease [7]. Many metabolites are known to play an intermediate, gene-and environment-dependent role in the etiology of complex traits.…”
Section: Introductionmentioning
confidence: 99%